UPAYA TIONGKOK DALAM PEMBANGUNAN CHINA PAKISTAN ECONOMIC CORRIDOR (CPEC) SEBAGAI STRATEGI KEAMANAN ENERGI TIONGKOK TAHUN 2013 – 2017 - Devi Nugraha, Putu Ananda; Priadarsini, Ni Wayan Rainy; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT   This research aims to describes describes China's efforts in the development of the China Pakistan Economic Corridor (CPEC) as China's energy security strategy using qualitative research methods. This study uses two concepts, namely the concept of energy security to see the urgency of China in securing oil imports and China's grand strategy which explains that increased cooperation is carried out by China to achieve its interests. The results of this study indicate that the benefits obtained by Pakistan in the CPEC are China's efforts to suppress the emergence of problems in building an alternative routes for China's oil imports.   Keywords: China Pakistan Economic Corridor, Energy Security, China’s Grand Strategy